Nursing home administration - Allen, James E. (James Elmore), 1935- (Springer Pub., 2008)
Contains the knowledge essential to prepare for licensure and employment as a nursing home administrator. Using as its basis the guidelines of the National Association of Boards of Examiners of Nursing Home Administrators, this work includes sections on: Distinguishing delirium from dementia; Psychosis from agitation; GERD; and Glycemic control.